1998
DOI: 10.24266/0738-2898-16.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dolomitic Lime on Growth and Nutrient Uptake of Buddleia davidii ‘Royal Red’ Grown in Pine Bark

Abstract: Buddleia davidii Franch. ‘Royal Red’ was grown in pine bark amended with 0.0, 2.4, 4.7 or 9.5 kg/m3 (0.0, 4.0, 8.0, or 16.0 lbs/yd3) dolomitic lime. Growth characteristics responded quadratically to dolomitic lime with those plants receiving 2.4 kg/m3 having the greatest shoot and root dry weights and inflorescence numbers. Plants grown in 4.7 kg/m3 had the greatest shoot lengths. Concentrations of Ca and Mg in leaves of plants grown in containers without dolomitic lime amendment were below that recommended fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This could be at least partially the result of the increased pH observed with higher incorporation rates of steel slag. For example, Gillman et al (1998) reported reduced butterfl y bush growth in pine bark substrates amended with greater than 2.4 kg•m -3 (4 lb•yd -3 ) dolomitic lime. Butterfl y bush root ratings responded similarly to SDW with respect to the two control groups and slag rate.…”
Section: Resultsmentioning
confidence: 99%
“…This could be at least partially the result of the increased pH observed with higher incorporation rates of steel slag. For example, Gillman et al (1998) reported reduced butterfl y bush growth in pine bark substrates amended with greater than 2.4 kg•m -3 (4 lb•yd -3 ) dolomitic lime. Butterfl y bush root ratings responded similarly to SDW with respect to the two control groups and slag rate.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Altland et al (2015) using a 80 pine bark : 20 peatmoss (by volume) substrate showed a curvilinear response in pH to DL rate over the range of 0 to 4.8 kgÁm -3 , but doubling or tripling the rate up to 14.3 kgÁm -3 resulted in little or no additional change. Likewise, Gillman et al (1998) reported a pH increase in 100% pine bark from 4.4 up to 6.1 with 4.8 kgÁm -3 DL, but only up to 6.4 when the rate was doubled to 9.5 kgÁm -3 . Harvey et al (2004) reported that 3.6 kgÁm -3 DL raised pH of a 3 pine bark : 2 peatmoss : 1 sand (by volume) substrate from 3.7 to 6.2, whereas more than doubling the rate up to 9.5 kgÁm -3 only raised the pH an additional 0.9 units up to 7.1.…”
Section: Dolomitic Lime Rate Affects Substrate Phmentioning
confidence: 89%
“…Walden and Epelman (1988) Chrustic and Wright (1983) reported that shoot N was higher in 'Helleri' holly (Ilex crenata), 'San Jose' juniper (Juniperus chinensis), and 'Rosebud' azalea (Rhododendron obtusum) at lower DL rates and attributed greater growth of these crops a low lime rates to greater N, phosphorus (P), and K availability. Gillman et al (1998) reported 'Royal Red' butterfly bush (Buddleia davidii) foliar N was highest in nonlimed controls; however, trends in shoot N with increasing DL rates did not follow a clear pattern. In contrast, Nash et al (1983) reported similar shoot N levels among limed and nonlimed photinia (Photinia •fraseri).…”
Section: Substrate Ph Affects Nitrogen Dynamicsmentioning
confidence: 94%
See 2 more Smart Citations